KIC 7599132: an ellipsoidal variable in a close SB1 system. Issue 2 (17th March 2018) - Catanzaro, G; Frasca, A; Giarrusso, M; Ripepi, V; Leone, F; Tognelli, E; Munari, M; Scuderi, S
Abstract: In this paper, we present a spectroscopic and photometric analysis of the suspected ellipsoidal variable star KIC 7599132. New spectroscopic observations have been obtained with Catania Astrophysical Observatory Spectropolarimeter. From the fit of Hα and Hβ, we determined the effective temperature and gravity of the primary component, T eff = 10200 ± 150 K and log g = 4.1 ± 0.1, while from a number of metal lines, we derive the rotational velocity, v e sin i = 60 ± 2 km s −1 . We found almost solar abundances with the exception of silicon (0.50 dex) overabundance. A Bayesian analysis, based on the comparison between observational data and theoretical predictions of PROSECCO evolutionary models, allows us to estimate the mass and the age of the primary. We obtained M 1 = 2.4 ± 0.2 M⊙ and τs = 3.8 _-0.7^+0.9 Myr. A new model for the system was obtained combining Kepler photometric time series (Q0–Q17) and our radial velocities by using the code phoebe . As a result, the system appears to be a detached binary system with a mass ratio q = 0.30 ± 0.01, a semimajor axis a = 7.3 ± 0.1 R⊙ and an inclination angle i = 35° ± 2°. This modelling allowed us to derive: M 2 = 0.7 ± 0.1 M⊙, R 1 = 3.0 ± 0.2 R⊙, and R 2 = 1.5 ± 0.2 R⊙ . Numerical simulations show that if the secondary star had been hotter than 4000 K, we would have observed its spectral features in our spectra.